The Senkaku Islands Dispute: Four Reasons of the Chinese Offensive - A Japanese View. Issue 1 (2nd January 2019) - Sato, Koichi
ABSTRACT: This article introduced China's four reasons of offensive to the Senkaku Islands: the first reason China's natural resources demand; the second reason historical issues with Japan that have some relationship to Chinese people's wartime memories; the third reason the Senkaku Islands Dispute as a tool of Chinese Communist Party (CCP)'s internal power struggle; the fourth reason the Senkaku Islands Dispute as a tool of CCP for China's national integration. Some reasons of Chinese offensive have been intertwined with each other, though the first reason is the main issue and the origin of the Senkaku Islands Dispute. It seems that other three reasons are supportive reasons for the natural resources demand, and byproducts of the dispute between Japan and China. The author discusses the occurrence and changes of these four reasons and concludes that the third and fourth reasons will be more troublesome than the others because they are unpredictable.